Steal This Classroom Teaching and Learning Unbound - Cohen, Jody (punctum books, 2019)
Jody Cohen and Anne Dalke construe "classrooms" as testing grounds, paradoxically boxed-in spaces that cannot keep their promise to enclose, categorize, or name. Exploring what is usually left out can create conditions ripe for breaking through, where real and abstract reverse and melt, the distinction between them disappearing. These are ecotones, transitional spaces that are testing grounds, places of danger and opportunity.In college classrooms, an urban high school, a public library, a playground, and a women's prison, Anne and Jody share scenes where teaching and learning take them by surprise; these are moments of uncertainty, sometimes constructed as failure. Digging into and exploding such moments reveals that they might be results of institutional pressures, socioeconomic and other diversities not acknowledged but operating and entangling individuals and ideas. Classrooms are sometimes "stolen" by the complex systems surrounding and permeating the activities that take place there; Jody and Anne explore ways to steal them back. Examining what is hidden but present in such moments can turn them into breakthroughs, powerful learning for educators and students-revealing how failure itself might not be what it seems.Moving back and forth between micro and macro in a continual interplay across individuals, groups, and institutions, and organizing their experiences and philosophies of teaching under the rubrics of Playing, Haunting, Silencing, Unbecoming, Leaking, Befriending, Slipping, and Reassembling, Anne and Jody try out alternative tales, exploring a pedagogical orientation that is ecological in the largest sense, engaging teachers and students in re-thinking learning and teaching in classrooms, and in their larger lives, as complex, enmeshed, volatile eco-systems.